PENGARUH INFLASI, SUKU BUNGA DAN HARGA MINYAK DUNIA TERHADAP HARGA SAHAM SEKTOR PERBANKAN TAHUN 2021-2024 - Karen Karen; Jocelyn Griselda Nababan; Thomas Firdaus Hutahaean; Hotma Mentalita (JURNAL LENTERA BISNIS, 2026)
This research aims to examine the effect of inflation, interest rates, and global oil prices on banking sector stock prices in 2021-2024. This study uses associative research. The population was 43 banks listed on the Indonesia Stock Exchange (IDX) for the 2021-2024 period. The sample consisted of 43 data sets. The analysis technique used was multiple linear regression. The results show that inflation (X1) has no effect on banking sector stock prices in 2021-2024, interest rates (X2) has no effect on banking sector stock prices in 2021-2024, global oil prices (X3) has no effect on banking sector stock prices in 2021-2024, and inflation, interest rates, and global oil prices simultaneously affect banking sector stock prices in 2021-2024.